The Development of Knowledge Management Model in Supervision, Monitoring and Evaluation of Educational Management of the Primary Education Service Area Office - Tiamvong, Veerapong; Ruangmontri, Karn (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to develop the knowledge management model in supervision, monitor and evaluate educational management of the Primary Education Service Area Office including to evaluate the application of the knowledge management model in supervision, monitor and evaluate educational management of the Primary Education Service Area Office. This study was conducted with research and development with 3 phases of implementation, namely: Phase 1 Study of current conditions, problems and needs; Phase 2 Development of the knowledge management model in supervision; and Phase 3 Evaluation of applying the knowledge management model in supervision. The findings indicated that the knowledge management model in supervision, monitor and evaluate educational management of the Primary Education Service Area Office consists of 2 steps which are knowledge building; knowledge gathering; knowledge applying; knowledge sharing and exchanging; and knowledge evaluation. Framework of supervision, monitoring and educational evaluation comprises 5 aspects, namely: research system; supervision system; learning resource and innovative media systems; facilitation system; and participation system. The implementation plan features an action meeting for studying the current conditions, problems and needs; defining teams based on learning; activity implementation in accordance with the knowledge management handbook; seminar on implementation summary and revision of knowledge base; and presentation of implementation of each knowledge base. The evaluation of consistency, suitability, feasibility on practice and usefulness of the knowledge management in supervision was at the highest level. In addition, the evaluation of applying the knowledge management in supervision gained efficiency of process and effectiveness of the result as 85.44/80.25. The research team had satisfaction towards the implementation at the highest level.